Molecular Dynamics Simulations of Micelle Formation around Dimeric Glycophorin A Transmembrane Helices - Braun, Rosemary (Biophysical Society, 2004)
Insertion and formation of membrane proteins involves the interaction of protein helices with one another in lipid environments. Researchers have studied glycophorin A (GpA) transmembrane helices embedded in sodium dodecyl sulfate (SDS) micelles to identify contacts significant for helix dimerization. However, a detailed picture of the conformation and dynamics of the GpA-SDS system cannot be obtained solely through experiment. Molecular dynamics simulations of SDS and a GpA dimer can provide an atomic-level picture of SDS aggregation and helix association. We report 2.5-ns simulations of GpA wild-type and mutants in a preformed micelle as well as a 32-ns simulation showing the formation of a complete micelle around wild-type GpA from an initially random placement of SDS molecules in an aqueous environment. In the latter case, an initial instability of GpA helices in water is reversed after the helices become surrounded by SDS. The properties of the spontaneously formed micelle surrounding the GpA are indistinguishable from those of the preformed micelle surrounding the GpA dimer.